A real world comparison of sulfonylurea and insulin vs. incretin-based treatments in patients not controlled on prior metformin monotherapy - Gitt, Anselm Kai; Bramlage, Peter; Schneider, Steffen; Tschöpe, Diethelm (Cardiovascular diabetology, 2015)
Metformin is the first line drug for patients diagnosed with type-2 diabetes; however, the impact of different treatment escalation strategies after metformin failure has thus far not been investigated in a real world situation. The registry described herein goes some way to clarifying treatment outcomes in such patients.